When Politics Drive Program Innovation (Journal of Education and Development, 2018)
This article presents a discussion of the evaluation of an educational intervention introduced by the Ministry of Education in response to social and political pressure. The social protest that started in Israel during the summer of 2011 addressed a variety of social issues, lasted through 2016 and led to the Ministry of Education decision to open a new training programme for teachers. One of the aims of the intervention was to provide an additional adult in classrooms of more than 32 pupils. To meet this goal, the Ministry required third-year student teachers to work at schools co-teaching with the classroom teacher three days a week. Twenty-five institutions of higher learning representing 81 cities and communities responded “yes” to the call for a pilot programme. Using mixed methods, the evaluation of the pilot was attentive to the voices of all participants and revealed the complexity of the programme. The conclusions and suggestions of the evaluation were supposed to feed into a policy decision, but unfortunately did not. Through a presentation of the evaluation of the programme and the issues it raised, the article contributes a significant example of how political constraints prevent institutions from dealing with evaluation conclusions and unintended outcomes of programs.